Efektivitas Edukasi Kesehatan Menggunakan Metode Simulasi dengan Media Flipchart Terhadap Tingkat Pengetahuan dan Self-Efficacy untuk Tidak Merokok pada Siswa SMKN 01 Palopo - Adestia Dahlan (YICI Publisher, 2024)
Cigarettes are inanimate objects that attack the health of the human body for the long term. Smoking behavior is very difficult to eliminate, but we can minimize it by intervening with potential smokers (children to adolescents), because those with young age are vulnerable to being influenced by the surrounding environment. WHO estimates that smokers in the world aged 15 years and over already number 1,100,000,000. Therefore, it is necessary to intervene so that they are not easily influenced by providing health education, one of which is the simulation / practice method of props with flipchart media. Objective: This study aims to determine the effectiveness of health education using the simulation method with flipchart media on the level of knowledge and self-efficacy not to smoke in students of SMKN 1 Palopo in 2024. Methods: This study is a type of quantitative research using a pre experimental approach with a one group pretest posttest design. The population in this study were all students of SMKN 1 Palopo in 2024 as many as 1244 respondents. The sampling in this study used the finite population survey formula (slovin), until the resulting sample size was 302 respondents. Data collection uses instruments in the form of questionnaires distributed in the form of links. The data that has been collected is then processed and analyzed using a statistical program (SPSS), which data analysis consists of univariate analysis to determine frequency distribution and bivariate analysis using the Wilcoxon test with a significance level (0.05). Results: The use of simulation method with flipchart media is effective on the level of knowledge and self-efficacy not to smoke in students of SMKN 1 Palopo, with a significant value (p = 0.000), after being given health education. Conclusion: Health education using the simulation method with flipchart media is effective on the level of knowledge and self-efficacy of students of SMKN 1 Palopo not to smoke.